2021
DOI: 10.3390/toxics9030066
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Contamination Index and the LWPI Index to Assess the Quality of Groundwater in the Area of a Municipal Waste Landfill

Abstract: Environmental degradation caused by the migration of pollutants from landfills is one of the biggest problems for urban areas. Systematic monitoring of groundwater in the vicinity of waste dumps allows for an assessment of the degree of risk to the soil and water environment. In this paper, spatiotemporal variation of groundwater pollution near a municipal landfill in Sosnowiec (southern Poland) was investigated. For this purpose, the monitoring results of five physicochemical indicators from 2014–2019 were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Similar research was performed in the region of the landfill in Sosnowiec (southern Poland). The results of contamination index determined by the Backman method based on data from the monitoring of groundwater in 2014-2019 from the municipal landfill indicate high groundwater contamination in its area (Knopek and Dąbrowska, 2021). There, the C d index was determined on the basis of the parameters that most exceed the criteria of the Regulation of the Minister of Maritime Economy and Inland Navigation of October 11, 2019, on the criteria and method of assessing the status of groundwater bodies, i.e., EC, SO 4 2-, Cl -, Na + and Fe 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar research was performed in the region of the landfill in Sosnowiec (southern Poland). The results of contamination index determined by the Backman method based on data from the monitoring of groundwater in 2014-2019 from the municipal landfill indicate high groundwater contamination in its area (Knopek and Dąbrowska, 2021). There, the C d index was determined on the basis of the parameters that most exceed the criteria of the Regulation of the Minister of Maritime Economy and Inland Navigation of October 11, 2019, on the criteria and method of assessing the status of groundwater bodies, i.e., EC, SO 4 2-, Cl -, Na + and Fe 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Studies (Backman et al, 1998) using the contamination index show that the water-quality parameters reflect the influence both of natural and anthropogenic environmental factors on groundwater quality. The authors of the latest research (Knopek and Dąbrowska, 2021) using this index state that the use of this measure to assess the vulnerability of groundwater to pollution is correct, although this indicator in compared to the Landfill Water Pollution Index is more sensitive to changes in the background value for described by them landfill. The authors of this article obtained the index value exceeding 1400.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of these parameters and weights to calculate the LWPI was made based on the data obtained in the different studies. Table 1 presents the weight of the parameters used in this study (7)(8)(9)(10)(11). Table 2 shows the groundwater quality class based on LWPL (8).…”
Section: The Landfill Water Pollution Indexmentioning
confidence: 99%
“…The study conducted in Southern Poland showed five physicochemical parameters of water used during 2014-2019. This study is an example of using LWPI and Cd for evaluating groundwater quality (10). In another study, Talalaj IA surveyed groundwater quality using modified LWPI.…”
Section: Introductionmentioning
confidence: 99%
“…These ordinances focus mostly on the provisions concerning testing for specific electrical conductivity (EC), pH, total organic carbon (TOC), copper, zinc, lead, mercury, cadmium, chromium, and total polycyclic aromatic hydrocarbons. However, in the case of many landfills, some of these elements -such as mercury or chrome -are found in concentrations below the limit of quantification (Wdowczyk and Szymańska-Pulikowska, 2020;Knopek and Dąbrowska, 2021). Therefore, increasing attention is paid to other parameters that are typical indicators of groundwater pollution in the hazard area (Slack et al, 2007).…”
Section: Introductionmentioning
confidence: 99%